Análise técnica e regulatória da geração de energia a partir do biogás de aterros sanitários no Espírito Santo - Galiza, Juçara de Jesus Monteiro de (2017)
The use of biogas generated from anaerobic digestion of Solid Urban Waste (SUW)reveals itself as an important option for diversifying the brazilian energetic sources plus reducing the impact of solid waste on the environment. So, this study tried to estimate the potential for biogas generation in the landfills in the state of Espírito Santo aiming to evaluate it ́s energetic potential in the creation ofelectric energy.Also it analysisregulatory possibilities for commercialization and the use of this resource in Brazil and especially in EspíritoSanto and it ́s macro regions. Regarding methodology this research used in it ́s quantitative phase the gatheringof information on operational landfills and a projection for waste generation for Espírito Santo to be included in Model Land GEM recommended by United States Environmental Protection Agencyfor prevision of biogas generation potential. In it ́s qualitative phase of energy commercialization regulation analysis, was used bibliographical and documental research. We also used interviews with representatives of the energy sector and plants. The results indicate that the available energy for supply in the periodfrom 2016 to 2035 is approximately 3.17 x 109kWh,an annual average of 158.687 MWh/year, capable to attend to 88.160 households. Based on regulatory analysis was noted the feasibility for use in experimental and industrial forms as well as for dedicated use and vehicular fuel in captive fleets. However, in the present time national regulations make it unfeasible the use of this resource in the natural gas (NG) network.